"Alligators All Around" and the ICD-10 code set. (14th February 2017) - Legatt, Alan D.
Abstract : With the changeover from ICD-9 to ICD-10 codes has come a tremendous expansion in the number of diagnosis codes, from 14, 025 to 69, 823, 1 covering an amazing number of conditions. One newspaper story I read pointed out that there are codes for being bitten by an alligator and for being sucked into a jet engine. I investigated further, 2 and found out that there are actually 12 separate codes for encounters with an alligator (table 1). It is surprising that there are not separate codes for alligator-related injuries to the left vs the right side of the body, given the ICD-10 penchant for identifying laterality whenever possible (and even when it is not possible—there are separate codes for aneurysmal subarachnoid hemorrhage from the "left anterior communicating artery, " I60.22, from the "right anterior communicating artery, " I60.21, and from an "unspecified anterior communicating artery, " I60.20).